EFFECTS OF IRON AND COPPER OXIDE NANOPARTICLES ON CALLUS INDUCTION AND IN VITRO REGENERATION OF POTATO (SOLANUM TUBEROSUM L., CV. TELMAN) - Nasibov, H. N.; Hasanzada, A. V.; Quluzada, Z. N.; Bronnikova, L. I. (НДУ ім. М. Гоголя, 2026)
Potato is widely used as a model species for plant tissue culture, micropropagation, and genetic improvement studies due to its responsiveness to in vitro manipulation and its economic relevance. Iron (Fe) and copper (Cu) are essential micronutrients involved in fundamental physiological and biochemical processes in plants. The application of metal oxide nanoparticles has recently emerged as a promising strategy to improve nutrient bioavailability and morphogenic responses in plant tissue culture. This study investigated the effects of iron oxide (Fe₃O₄) and copper oxide (CuO) nanoparticles on callus induction and in vitro regeneration of potato (Solanum tuberosum L., cv. Telman). Explants cultured on Murashige and Skoog (MS) medium supplemented with optimal concentrations of Fe and Cu nanoparticles exhibited significantly enhanced callus formation, shoot regeneration, and rooting compared to the control. In contrast, higher nanoparticle concentrations negatively affected morphogenesis, likely due to nanoparticle-induced oxidative stress. These results demonstrate the potential of iron and copper oxide nanoparticles as effective modulators of potato tissue culture when applied at appropriate concentrations. Results suggest that nanoparticles not only influence early morphogenic responses but also have lasting effects on plantlet establishment, which is critical for successful transfer from in vitro to ex vitro conditions. Controlled application of Fe₃O₄ and CuO nanoparticles therefore represents a promising strategy for improving tissue culture efficiency in potato. Overall, the data indicate that the effects of nanoparticles on potato tissue culture are dose-dependent, with low to moderate concentrations enhancing callus induction, shoot regeneration, and root development, while higher concentrations impose inhibitory effects due to oxidative stress. Plantlets regenerated under optimal nanoparticle treatments exhibited enhanced rooting performance and higher survival rates during acclimatization. However, elevated concentrations of Cu-NPs resulted in a pronounced decrease in regeneration efficiency. This decline suggests potential copper-induced toxicity, likely associated with the disruption of cellular redox homeostasis and excessive ROS accumulation.
Keywords: Solanum tuberosum, iron oxide nanoparticles, copper oxide nanoparticles, callus induction, in vitro regeneration, nanobiotechnology